Internet sentiment to public health emergencies: current situation and response strategies in China - Yu-qing MI; Min JIAO; Zhen-de WANG (Editorial Office of Chinese Journal of Public Health, 2022)
ObjectiveTo examine current situation of internet sentiment on public health emergencies and strategies for coping with the situation in China to provide evidence for administrative agencies' effective response to the public sentiment. MethodsPublished studies relevant to internet sentiment on public health emergency published in Chinese or English up to October 30th, 2021 were retrieved through comprehensively searching Chinese National Knowledge Infrastructure (CNKI), Wanfang Database and PubMed. Content analysis, co-word clustering and significance assessing were used to sort out and categorize the characteristics of internet sentiment on public health emergencies and strategies and problems in administrative agencies' response to the sentiment. Ordinal ranking was adopted to evaluate the importance and severity of the strategies and problems in the agencies' responses. Results Based on content analysis on 116 literatures included into the study, 29 features were identified in terms of public health emergency-related internet sentiment's ontology, subject, content, development, communication, society, space and time. Also according to the analysis, 25 problems and 26 strategies in the responses to the internet sentiments were revealed at four stages of prevention, preparation, response and recovery in dealing with a public health emergency. The ordinal ranking for the importance/severity of the 25 problems and 26 response strategies were basically consistent in the 4 stages of public health emergency management; the top serious problems in each stage were delayed management and prevalence of rumors due to the lack of initiative in response stage, without theoretical guidance owing to imperfect laws and regulations in preparation stage, lacking post-event evaluation and accountability as a result of imperfect systemic infrastructure in recovery stage, and too much information noise due to the absence of serial theme propaganda in prevention stage, with the severity/importance index score of 0.1263, 0.0982, 0.0355, and 0.0305; the top important strategies in each stage included dispelling rumors actively in mass media in response state, establishing a mechanism to deal with the internet sentiment in preparation stage, establishing regulations for rapid evaluation and accountability about the internet sentiment in recovery stage, and constructing a media-wide communication system for carrying out positive publicity actively in preparation stage, with the severity/importance index score of 0.1062, 0.1016, 0.0360, and 0.0257, respectively. Conclusion The response to public health emergency-related internet sentiment should be integrated into the whole process responding to public health emergencies and should be addressed in each of the four stages: prevention, preparation, response and recovery. Such considerations should be aligned with risk communication strategies for public health emergency response, for better resolving of social contradictions and satisfying of public needs.